Learning Symmetrical Relations Facilitates Emergence of Intraverbals after Reading a Text: Effects on Reading Comprehension. - Pérez-González, Luis Antonio; Oltra, Javier (Psychological Record, 2023)
We studied the effect of prior learning of symmetrical intraverbals on the emergence of complex intraverbals after reading a text. In Experiment 1, eighteen 7- and 8-year-old children read a text with sentences in which A and B stimuli and B and C stimuli were related (e.g., "The Alps" to "Mont Blanc," and to "Falcon"). Thereafter, all ABC intraverbals (e.g., C–A—"Name the mountain range of the falcon") were probed without reinforcement with written stimuli and written responses. In Condition 1, six children learned before intraverbals that relate the categories to the exemplars that served as stimuli in the text (e.g., "Name a mountain"—"Mont Blanc"—Exemplars) and learned intraverbals that relate the exemplars to the categories (e.g., "What is the Mont Blanc?"—"A mountain"—Categories.) In Conditions 2 and 3, 12 children did not learn Categories or neither Exemplars and Categories. All children in Condition 1 demonstrated the emergence of all ABC intraverbals, but not all children in Conditions 2–3 demonstrated emergence. Experiment 2 controlled that text presentations and teaching trials did not affect the results and replicated the effect. Therefore, learning simple discriminations symmetrical to one another facilitates further emergence with more complex discriminations—intraverbals—which evidence reading comprehension.